Mechanical modeling and powder characteristics of wheat milling process: A comparative study of roller, hammer and stone mills - Chi Zhang; Jiyun Hu; Qin Xu; Haihong Zhang; Rangling Li; Junhao Guan (Journal of Agriculture and Food Research, 2025)
This study systematically compared the influence mechanisms of three milling methods: roller mill, hammer mill, and stone mill, on the properties of wheat flour. The relationship between different crushing mechanisms and flour properties was elucidated by establishing a mechanical model of the milling process, complemented by laser particle size analysis and scanning electron microscopy characterization. The results showed that the roller mill was dominated by extrusion-friction composite effect, the hammer mill was dominated by high-speed impact crushing, and the stone mill realized milling through friction-shear synergistic effect. The particle size distribution characteristics indicated that both roller-milled and stone-milled flours exhibited a bimodal distribution with high concentration (D90 < 160 μm), while hammer-crushed flour, although also bimodal, had a broader particle size distribution (D90 > 200 μm). Microscopic morphology analysis revealed that roller-milled flour had the highest surface smoothness and regular particle morphology; hammer-crushed flour exhibited irregular fracture surfaces and more fine debris; and stone-milled flour showed significant grooves and layered fragmentation features. This study analyzed the mechanical characteristics of the milling process, the particle size distribution and morphological characteristics of the powder, and provides a theoretical basis for the optimization of wheat processing technology and the development of special powder.